Robustness increases heritability: implications for familial disease. (16th January 2023) - Frank, Steven A
Abstract: Robustness protects organisms in two ways. Homeostatic buffering lowers the variation of traits caused by internal or external perturbations. Tolerance reduces the consequences of bad situations, such as extreme phenotypes or infections. This article shows that both types of robustness increase the heritability of protected traits. Additionally, robustness strongly increases the heritability of disease. The natural tendency for organisms to protect robustly against perturbations may partly explain the high heritability that occurs for some diseases.